Treatment of produced water by simultaneous removal of heavy metals and dissolved polycyclic aromatic hydrocarbons in a photoelectrochemical cell - Igunnu, Ebenezer Temitope (2014)
Early produced water treatment technologies were developed before carbon dioxide emissions and hazardous waste discharge were recognised as operational priority. These technologies are deficient in the removal of dissolved hydrocarbons and dissolved heavy metal ions which have been identified as major contributors to the high environmental impact factor of produced water. The simultaneous removal of heavy metals and polycyclic aromatic hydrocarbon (PAH) from produced water via photoelectrochemical process was identified in this work as a produced water treatment alternative with the potential to virtually eliminate the cost for chemical reagents and high energy input.